Local and global cooperativity in the human alpha-lactalbumin molten globule. - Quezada, C; Schulman, B; Froggatt, J; Dobson, C; Redfield, C (2004)
NMR spectroscopy has been used to follow the urea-induced unfolding of the low pH molten globule states of a single-disulfide variant of human alpha-lactalbumin ([28-111] alpha-LA) and of two mutants, each with a single proline substitution in a helix. [28-111] alpha-LA forms a molten globule very similar to that formed by the wild-type four-disulfide protein, and this variant has been used as a model for the alpha-lactalbumin (alpha-LA) molten globule in a number of studies. The urea-induced unfolding behavior of [28-111] alpha-LA is similar to that of the four-disulfide form of the protein, except that [28-111] alpha-LA is less stable and has greater cooperativity in the loss of different elements of structure. For one mutant, L11P, the helix containing the mutation is highly destabilized such that it is completely unfolded even in the absence of urea. By contrast, for the other mutant, Q117P, the helix containing the mutation retains its compact structure. Both mutations, however, show significant long-range destabilization of the overall fold showing that the molten globule state has a degree of global cooperativity. The results reveal that different permutations of three of the four major alpha-helices of the protein can form a stable, locally cooperative, compact structural core. Taken together, these findings demonstrate that the molten globule state of alpha-LA is an ensemble of conformations, with different subsets of structures linked by a range of long-range interactions.